Pendampingan Tahsin Al Qur’an Menggunakan Metode Baghdadi Pada Anak Panti Asuhan Budi Mulia Kabupaten Kediri - Mahfud Aziz Dhulkurnaen Husein; Isma Nurrokhim; Lukman Hakim; Oktavia Miftahul Farah; Reisa Himmatul Ulya (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This article describes community service activities in helping children at the Budi Mulia orphanage, Kalang Hamlet, Paron Village, Ngasem District, Kediri Regency in improving their reading of the Qur'an. The purpose of writing this article is to describe the community service activities carried out in helping children at the Budi Mulia orphanage in improving their reading of the Qur'an using the Baghdadi method. The method used in this activity is PAR (Participatory Action Research) which contains activities in the form of understanding real conditions, understanding problems, planning, action and evaluation. The results obtained are that the community, orphanage administrators and local government appreciate and find that the results of student activities play a very important role in helping to improve the reading of children at the Budi Mulia orphanage. The conclusion of the activity is that the reading of the Qur'an of the children at the Budi Mulia orphanage in Kediri is getting better.